Applied Economics, Business and Development International Symposium, ISAEBD 2011, Dalian, China, August 6-7, 2011, Proceedings, Part I - Zhou, Qingyuan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This four-volume-set (CCIS 208, 209, 210, 211) constitutes the refereed proceedings of the International Symposium on Applied Economics, Business and Development, ISAEBD 2011, held in Dalian, China, in August 2011. The papers address issues related to Applied Economics, Business and Development and cover various research areas including Economics, Management, Education and its Applications.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information systems; Artificial intelligence; Computer Science; e-Commerce/e-business.; Information Systems Applications (incl.Internet).; Computer Communication Networks; Computers and Society; Artificial Intelligence (incl. Robotics).; Software Engineering